From the imprescribility of the fundamental human right to due process, to contradictory and the broad defense (Research, Society and Development, 2021)
In the Brazilian procedural reality, among the fundamental rights that stand out are the principles of due process, contradictory and broad defense, especially raised to the category of human rights listed by the text of the Federal Constitution of 1988. In this sense, it is indispensable to analyze some issues specific to these constitutional statements, given the importance of such institutes for the structuring and development of the process in a valid and regular manner, without stain of any nature. Therefore, through scientific research, based on qualitative methodology of bibliographic review, it is intended, with this article, to demonstrate the imprescriibility of material pretension resulting from violation of fundamental human rights, regardless of the democratic, authoritarian or totalitarian political regime in force at the time of the practice of the administrative act contrary to the Brazilian constitutional principle, using even jurisprudential research,  as a way to bring up the understanding of the Superior Court of Justice (STF) regarding the proposed theme, in view of the extent of the legal and social repercussion that the pronouncement of the Superior Court can achieve in the fields of interpretation and application of positive law and in the relations of politically organized society.